Artyści pańszczyźniani w Rosji - Mucha, Bogusław (Rusycystyczne Studia Literaturoznawcze, 2016)
In Russian culture of the XVIII and XIX century turn, artists who derived from the peasant social class, played an important part. Until 1861 they have been deprived of their personal liberty and they were owned by the nobility. Very little can be found on the topic in literature. This article describes those artists’ achievements in painting, architecture, theatre and music. They were active both in the country and in big cities.